COMPARISON OF THE ANTIBACTERIAL ACTIVITY OF COW MILK KEFIR AND GOAT MILK KEFIR AGAINST BACTERIA BACILLUS CEREUS - Suhartanti, Dwi; Septian, Ryan (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2014)
Background: Kefir is fermented milk and comes from the Caucasus. Kefir is made by inoculating cow milk, goat or sheep with kefir grain. Kefir contains 0.5?1.0% alcohol and 0.9 to 1.1% lactic acid. This product is very popular in the Soviet Union, where the consumption of kefir reach 4.5 kg per capita per year. Kefir made from pasteurized milk and fermented with kefir grain, kefir grain is white seeds from bacteria colony, such as Streptococcus sp., Lactobacilli and some types of yeast/yeast apatogen. As a probiotic drink, kefir contains bacteria of lactic acid and acetic acid bacteria in kefir are giving acidity and produces secondary metabolites that bacteriocins that kill pathogenic bacteria such as Bacillus cereus.Method: This study used cow milk and goat milk kefir as a starting material, to produce a cow milk kefir and goat milk kefir. Cow milk kefir and goat milk kefir were compared antibacterial activity against Bacillus cereus. Previously each made 3 variations of the concentration of 2%, 4%, and 6% kefir grains were added cow milk and goat milk. Antibacterial activity tested using Kirby Bauer method so that the observation a clear zone formed on the media was the inhibition activity of the bacterium Bacillus cereus. The results were analyzed by ANOVA, Mann Whitney, and Tukey with a significance of 95%.Result: The results showed that goat milk kefir has better antibacterial activity against Bacillus cereus compared to cow milk kefir. Goat milk kefir with kefir seeds concentration of 6% has the best antibacterial activity with inhibition zone diameter of 6 mm. Keywords: kefir, Bacillus cereus, cow milk, goat milk